Development of Transmission Error Dynamic Testing Machine for Plastic Gear - Zhaoyao Shi; Xinli Ren; Bo Yu; Haizhou Li; Lintao Zhang; Yong Ye; Ping Li (Jixie chuandong)
Based on the principle of single flank measurement, a dynamic testing machine for plastic gear transmission error is developed and can simulate the actual working condition of the plastic gear and realize the dynamic measurement of transmission error under the condition of no-load, load and different speed of plastic gear with different parameters. The working principle, configuration and design of key parts of the testing machine are mainly introduced. The dynamic measurement test of the transmission error is carried out, and the variation of the transmission error at no load, load and different speeds is briefly analyzed. The test results show that the test machine can realize the fast measurement of plastic gear transmission error, which can improve the plastic gear transmission performance and provide scientific basis for the design and improvement of plastic gear.